(untitled) (Journal of Nepal Geological Society, 2011)
Rainfall triggered landslides are frequent problems in the residual soil of andesitic terrain in western Japan. Characteristics of residual soils over bronzite andesite, procedure of in situ permeability measurement, matric suction and soil moisture content change and stability analyses considering unsaturated-saturated soils as integral system are presented in this paper. The paper highlights two landslides of small andesitic hillock of western Japan and describes modelling of rainwater seepage, slope stability analysis and contributing parameters for landsliding in andesitic terrain. For both landslides, results of geomorphological and geotechnical analyses were used as a direct input to the numerical modelling. For transient conditions, a finite element analysis was used to model the fluctuations in pore water pressure during the rainfall, with the computed hourly rainfall rate as the surface boundary condition. This was then followed by the slope stability analysis using the temporal pore water pressure distributions derived from the seepage analysis. Obtained trend for the factor of safety indicates that the most critical time step for failure was a few hours following the antecedent moisture content of previously day peak rainfall. Time of failure estimated by modelling has shown good match with time declared by eyewitnesses.